Geometric Analysis of Nonlinear Partial Differential Equations - Lychagin, Valentin; Krasilshchik, Joseph (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book contains a collection of twelve papers that reflect the state of the art of nonlinear differential equations in modern geometrical theory. It comprises miscellaneous topics of the local and nonlocal geometry of differential equations and the applications of the corresponding methods in hydrodynamics, symplectic geometry, optimal investment theory, etc. The contents will be useful for all the readers whose professional interests are related to nonlinear PDEs and differential geometry, both in theoretical and applied aspects.